2006
DOI: 10.1007/s00464-006-9105-8
|View full text |Cite
|
Sign up to set email alerts
|

Friction dynamics of trocars

Abstract: For some trocars, friction can be as great as the forces associated with instrument-tissue interaction. At movement reversals, friction fluctuates due to deformations of the rubber and silicon parts of the sealing mechanism. Such high variance can deteriorate surgical performance during high precision tasks (e.g., tissue manipulation) that typically involve many changes in movement direction. Comparisons of the investigated trocars indicate that the friction magnitude and variance can be reduced easily by chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…He found that friction between instrument and trocar differed greatly among various designs of trocars. According to this study, the friction in the trocar varies between 0.25 and 3.0 N [20].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…He found that friction between instrument and trocar differed greatly among various designs of trocars. According to this study, the friction in the trocar varies between 0.25 and 3.0 N [20].…”
Section: Discussionmentioning
confidence: 91%
“…Some of these causes have already been investigated [19,20]. Sjoerdsma et al [19] focused on the mechanical transmission characteristics of four types of graspers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laparoscopic graspers were placed through a trocar (type Xcel 5; Ethicon ENDO-Surgery Inc., Cincinnati, OH, USA) with low friction to minimize the disturbance of forces caused by other elements [15]. Figure 1 shows the experimental setup for the condition of a laparoscopic grasper.…”
Section: Methodsmentioning
confidence: 99%
“…The transmission of forces from the tip of the instrument to the handle is limited and significantly disturbed, depending on the type of grasper and the kind of manipulation action (e.g. trocar friction, abdominal wall resistance, scaling factors, mechanical construction, and efficiency) [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%